«Que bon dictat era e verdader»: constants i divergències en els llibres de cuina medievals en llengua catalana. - SANTANACH SUÑOL, JOAN (Scripta)
The Catalan Tradition of Medieval Cookbooks comprises four recipe books dating from the mid-14th Century to the late 15th Century. In chronological order, they are The Book of Sent Soví, The Book of Food Preparation, The Book of Every Kind of Dish, and The Cook's Book by Mestre Robert. These works share various characteristics pertaining to their origins-they were authored by and intended for culinary professionals-as well as their transmission-their practical purpose meant that users significantly modified their content. The dynamic nature of the recipes contrasts with the data provided by their surviving copies: three of them are manuscripts transcribed by professional copyists, intended to be preserved in a library rather than direct usage in kitchens. The fourth book has only been preserved in print. The paper delves into the features of these books and highlights their principal similarities.